2019
DOI: 10.1093/ajcn/nqy384
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response relation between dietary sodium and blood pressure: a meta-regression analysis of 133 randomized controlled trials

Abstract: Background The projected reduced mortality effect of reduced sodium intake in model-based studies conflicts with the observed increased mortality associated with low sodium intake in population studies. This may reflect an overestimation of the dose-response relation between sodium reduction (SR) and blood pressure (BP) used in mortality modeling studies. Objectives The present meta-regression analysis sought to estimate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 30 publications
3
36
1
Order By: Relevance
“…Previous research, which consisted of a sample of Chinese adults (n = 6072) has already shown a concerning excessive sodium intake and an average consumption of sodium of 5.4 g/day [22]. Sodium maintains blood pressure, while consuming an excessive amount of sodium increases the risk of hypertension and NCD [4,24,25]. Although a recent study has shown that sodium consumption has been declining since 1982 in China [10], there are still some gaps comparing with the recommendations of the WHO [1].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research, which consisted of a sample of Chinese adults (n = 6072) has already shown a concerning excessive sodium intake and an average consumption of sodium of 5.4 g/day [22]. Sodium maintains blood pressure, while consuming an excessive amount of sodium increases the risk of hypertension and NCD [4,24,25]. Although a recent study has shown that sodium consumption has been declining since 1982 in China [10], there are still some gaps comparing with the recommendations of the WHO [1].…”
Section: Discussionmentioning
confidence: 99%
“…The determinants of our excessive salt appetite have been scarcely researched and, consequently, are scarcely understood (14)(15)(16)(17)(18) . Research has been primarily into the consequences of salt intake, primarily comprising large-scale studies, which have engendered the consensus that salt is toxic, along with a nuanced contention that it is less so (7,(9)(10)(11)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) .…”
Section: Critique Of Causes Of Salt Intake and Interventionmentioning
confidence: 99%
“…Therefore, it is moot whether reduction is intervention-related any more than the parallel decrease in total energy intake, to which Na intake is inextricably linked (45,46) . Further, failures and contradictory data for the same countries in line with global increases or stability have also been reported (14,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)42,(47)(48)(49)(50)(51) .…”
Section: Critique Of Causes Of Salt Intake and Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 There is also emerging evidence that salt reduction strategies are most effective when targeted to those in the highest quartile of intake and not the general population. 6 Second, the statement by the authors that "use of salt substitutes as a public health intervention warrants consideration as part of policy recommendations" is of great concern to us. Salt substitutes are one potential public health intervention to reduce sodium intake and increase potassium intake.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%